Assessment of the Knowledge and Approach of General Dentists Who Treat Children and Pediatric Dentists Regarding the Proper Use of Antibiotics for Children - Moran Rubanenko; Sigalit Blumer; Kayan Maalof; Shlomo Elbahary; Lazar Katz; Johnny Kharouba (Antibiotics, 2021)
Background: Antibiotics are widely used in dentistry. Dentists often provide antibiotics unnecessarily. Excessive use can induce resistant bacterial strains. There are certain indications for the proper use of antibiotics for pediatric dentistry according to the European and American Pediatric Dentistry (EAPD and AAPD). Very often dentists do not follow these guidelines. Objectives: This study aims to examine the level of knowledge among general dentists (who also treat children) and pediatric dentists on proper use of antibiotics. In addition, we examined whether there is unjustified use of antibiotics, if dentists are aware of the new and conservative approach of administering antibiotics to patients, and whether there is a relationship between years of professional seniority and dentist’s knowledge level of proper use of antibiotics. Methods: One hundred general dentists (GD) who treat children in addition to 100 pediatric dentists (PD) completed the study questionnaires which measured knowledge, practice and attitudes regrading using antibiotics during dental treatment among children. Results: The general average of level of knowledge on proper use of antibiotics among general dentists was relatively low for both GD (60.7%) and PDs (65%). PDs demonstrated a relatively greater knowledge of correct use of antibiotics, especially in cases of endodontics and trauma. PDs also showed higher awareness to latest guidelines for the admission of “prophylactic antibiotics” according to the American Association (AAPD) and/or the European Union (EAPD) compared with GDs (86.2% vs. 66.3%). Conclusion: The level of knowledge of both general dentists and pediatric dentists is poor, with a large percentage of dentists from both groups not knowing whether antibiotics are needed in a specific dental case or not. Compliance with the EAPD/AAPD guidelines is also low and inadequate. The method of prescribing antibiotics given by dentists can be improved by increasing awareness, educational initiatives, and postgraduate courses among dentists regarding the recommended indications.